Pengaruh Iklan Makanan dan Minuman di Berbagai Media Terhadap Preferensi dan Konsumsi Makanan Anak-Anak: Tinjauan Sistematis - Rahma, Aurellia; Yarna, Nafisah Shakira Putri; Rahma, Nurul; Maulaya, Najmah; J, Dea Fadhillah Ramanda; Yunaningsih, Septia; Pulungan, Rafiah Maharani (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Advertising exposure that directly or indirectly targets children as consumers can influence children's food preferences, especially for unhealthy foods and beverages. This systematic review was conducted to determine the effect of exposure to food and beverage advertisements on children's consumption preferences.Methods: A systematic review was conducted to determine the effect of exposure to food and beverage advertisements on children's consumption preferences. Article extraction was conducted on three databases (PubMed, Science Direct, Wiley), resulting in 11 articles for analysis.Result: As a result, children who watch TV >1.5 hours/day tend to choose cariogenic foods (OR=2.38). Food and beverage advertisements influence children's preferences in consuming unhealthy food and beverages, through the images and labels in the advertisement.Conclusion: Therefore, there is a need for regulations governing content standards in advertisements. Further research on the relationship of advertising airtime with children can be conducted to find out more about the aspects of advertising influence on children's food preferences.